BROADBAND MICROWAVE VIVALDI ANTENNA USING COPLANAR FEED LINE - Alexander A. Golovkov; Polina V. Terenteva; Alexander G. Zhuravlev; Michail S. Shmyrin; Nikolay S. Stenyukov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
Nowadays Vivaldi antennas are used as directional emitters with matching and balancing device at the input. As a rule, these devices cause additional losses in case of broadband operation. Besides, the use of the device leads to radiator pattern distortions, especially when operating in a wide frequency range. Stringent operating requirements (wide operating temperature, high humidity, salt fog, vibration, etc.), make the choice of proper chip very complicated. The aim of the study is to develop a slot antenna with a 50-ohm port at the input, which would be easy to manufacture and operate, while maintaining high gain in a wide frequency range. As is known, the field structure in the coplanar line is close to the field structure in the slit field close to it. As is known, the field structure in the coplanar line is similar to the field structure in the slot line. Using mathematics for such fields, means of electrodynamic modeling and numerical calculation, a system is developed that consists of two Vivaldi antennas fed by one coplanar line. Thus, the emitter has a close to a circular pattern and low losses in the structure of feeding, matching and balancing, the functions of which are performed by the coplanar line. The results are given for the frequency range of 1-6 GHz. The device as a whole is a dielectric substrate with radiating structure made as double-sided metallization. Finline-based emitters are acceptable to use for operation in higher frequencies. Antenna has low manufacturing cost and it is easy to repeat. Currently the authors are continuing work on the study of the use of such elements as part of antenna arrays.